Migrant healthcare workers during COVID-19: bringing an intersectional health system-related approach into pandemic protection. A German case study - Kuhlmann, Ellen; Ungureanu, Marius-Ionut; Behrens, Georg M. N.; Cossmann, Anne; Fehr, Leonie Mac; Klawitter, Sandra; Mikuteit, Marie; Müller, Frank; Thilo, Nancy; Brînzac, Monica Georgina; Dopfer-Jablonka, Alexandra (Frontiers in Public Health, 2023)
Introduction Migrant healthcare workers played an important role during the COVID-19 pandemic, but data are lacking especially for high-resourced European healthcare systems. This study aims to research migrant healthcare workers through an intersectional health system-related approach, using Germany as a case study. Methods An intersectional research framework was created and a rapid scoping study performed. Secondary analysis of selected items taken from two COVID-19 surveys was undertaken to compare perceptions of national and foreign-born healthcare workers, using descriptive statistics. Results Available research is focused on worst-case pandemic scenarios of Brazil and the United Kingdom, highlighting racialised discrimination and higher risks of migrant healthcare workers. The German data did not reveal significant differences between national-born and foreign-born healthcare workers for items related to health status including SARS-CoV-2 infection and vaccination, and perception of infection risk, protective workplace measures, and government measures, but items related to social participation and work conditions with higher infection risk indicate a higher burden of migrant healthcare workers. Conclusions COVID-19 pandemic policy must include migrant healthcare workers, but simply adding the migration status is not enough. We introduce an intersectional health systems-related approach to understand how pandemic policies create social inequalities and how the protection of migrant healthcare workers may be improved.